Efficiency enhancement of solar chimney power plant by use of waste heat from nuclear power plant. (10th April 2018) - Fathi, Nima; McDaniel, Patrick; Aleyasin, Seyed Sobhan; Robinson, Matthew; Vorobieff, Peter; Rodriguez, Sal; Oliveira, Cassiano de
Abstract: A solar chimney power plant (SCPP) offers an efficient method of converting solar irradiation to electrical power. It can be combined with a nuclear power plant to improve its efficiency and minimize its environmental impact. Rather than dumping the waste heat rejected by a nuclear power plant to a wet cooling tower, a better solution may be to connect it to an SCPP. This is particularly true in arid regions. The SCPP can serve the function of a dry cooling tower and produce additional electrical power. In a solar chimney power plant, the energy of buoyant hot air is converted to electrical energy. SCPP includes a collector at ground level covered with a transparent roof. The sun heats the air inside the collector and the ground underneath. A tall chimney is placed at the center of the collector, with a turbine located at the base of the chimney. In this investigation, the surplus heat from the nuclear cycle is used to increase the temperature of the air in the collector and therefore produce more electricity in the solar chimney power plant. The efficiency of the nuclear plant will be lowered due to the higher temperature of the condenser, but the loss can be made up by the increased power of the solar chimney. Heat from the sun is always free once the solar plant has been constructed and is not normally considered in the efficiency calculation. Computational fluid dynamics (CFD) and thermal analysis have been performed to apply the available surplus heat from the nuclear cycle and to measure the available kinetic energy of air for the turbine of the solar chimney power plant system. The feasibility of the system is evaluated, and the thermal efficiency of the combined power plant has been computed. By applying this idea to a typical 1000 MW nuclear power plant with a nominal 35.3% thermal efficiency, its efficiency can be increased to 42.0%. The combined cycle as presented is advantageous in environments where water is scarce. The cooling tower is replaced by the solar chimney power plant utilizing the surplus heat from the available warm steam in the secondary loop of the reactor. Highlights: Solar chimney power plant system (SCPPS) was introduced to nuclear power plant instead of cooling tower as a combined cycle. Computational fluid dynamics (CFD) and thermal analysis were performed to model and simulate this combined cycle. The overall thermal efficiency of a typical 1000 MW nuclear poweer plant was improved from 35.5% to 42%. The presented combined cycle is advantageous in environments where water is scarce.